저령차전자탕을 이용해 현훈을 치료한 환자의 특징 고찰 : 63례의 후향적 분석 - 정누리; 김기태; 신선미; 고흥; Jung, Nu-ri; Kim, Ki-tae; Shin, Seon-mi; Ko, Heung (대한한방내과학회지, 2019)
Purpose: The purpose of this study was to conduct a clinical analysis of patients treated for dizziness with Jeoreongchajeonja-tang, evaluate the effect of Jeoreongchajeonja-tang administration, and present indications of Jeoreongchajeonja-tang in dizziness. Methods: A retrospective study was conducted on 63 patients who were admitted to the Oriental Hospital of Se-Myung University from August 2012 to June 2019, complaining of dizziness, so who took Jeoreongchajeonja-tang. Results: 1) As a result of the analysis of the general characteristics of patients who took Jeoreongchajeonja-tang with dizziness, women were 2.7 times more than men. The age distribution was: patients in their 70s, 36.5%; in their 50s, 20.6%; in their 60s, 15.8%; and in their 80s, 12.6%. Patients had a history of hypertension (46.0%), diabetes (22.2%), stroke (17.4%), lung disease (12.6%), and cancer (11.1%). According to the diagnosis, 48 patients (76.1%) were assigned to the peripheral dizziness group, 7 patients (11.1%) to the central dizziness group, and 8 patients (12.6%) to other dizziness groups. 2) Compared with the peripheral dizziness group, the central dizziness group was older, their history of hypertension 8.4 times greater, their history of stroke 7.8 times greater, and the duration of herbal medicine administration was longer. 3) The vertigo grade was significantly decreased after taking Jeoreongchajeonja-tang (p=0.000). 4) As age increased by one year, odds ratio of improvement in the vertigo grade decreased by 0.924 times after taking Jeoreongchajeonja-tang (p=0.010). 5) Sex, disease duration, past history, diagnosis, the duration of herbal medicine administration, whether or not Yanggyuksanhwa-tang was combined with the Jeoreongchajeonja-tang and whether or not Western medicine was used did not affect improvement in the vertigo grade after taking Jeoreongchajeonja-tang. Conclusions: In patients with dizziness, Jeoreongchajeonja-tang can be used as a treatment without side effects.